Objelcti prometne infrastrukture u funkciji gospodarskog razvoja - Radačić, Željko; Šimulčik, Damir (Promet - Traffic&Transportation, 2012)
Traffic infrastructure makes an integral part of the traffic and economic system of each country. The designers of traffic infrastructure investment policy have to meet the requirement for this policy to be based on scientific developments and synchronized activity of all economic system segments. In the article the accent is assigned to the development and integration capability of traffic infrastructure facilities.